Achieving holistic sustainability in Chinese and New Zealand business partnerships : an integrative approach : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, Auckland, New Zealand - Chen, Michelle Sitong (Massey University, 2020)
Tensions in sustainability are a relatively new area and largely unexplored empirically between firms in collaborative business partnerships, particularly drawing from paradox theory and organisational ambidexterity theory. If these tensions cannot be understood and addressed adequately, it will not only have negative impacts on individuals’ interests, but also on the development of organisations and ultimately the prosperity of the society. Hence, this study examines empirically how tensions in addressing divergent sustainability issues arise, and are perceived and managed between Chinese and New Zealand firms in business partnerships. Guided by an interpretivist philosophy, this research adopts a qualitative and abductive approach as the preferred research method. In doing so, 33 in-depth individual interviews alongside one informal group discussion were carried out at 16 relatively large Chinese and NZ firms known for their commitment to sustainability that are in business partnerships. This thesis includes three empirical chapters. The first findings chapter identifies tensions in sustainability between Chinese and New Zealand firms and discovers the reasons for them. The findings reveal that the Chinese and New Zealand firms in business partnership are faced with complex and multiple sustainability tensions which are thus more difficult and challenging for them to address simultaneously. This chapter also shows that the tensions are caused by an integration of multiple reasons from individual, organisational and national levels. The second findings chapter explores how managers make sense of these tensions. The results delineate four kinds of managerial logic – paradoxical, contradictory, business and defensive – which are applied to make sense of different kinds of tensions. In contrast to prior studies, the findings reveal that paradoxical logic is the most common logic adopted by the managers at Chinese and NZ companies in business partnerships; as the other types – contradictory, business and defensive logic – are not commonly used. The third findings chapter investigates the strategies that Chinese and NZ firms adopted to manage the tensions in their business partnerships. The findings show two main approaches: trade-off and integrative. This research highlights that working through sustainability tensions using integrative approaches can bring proactive outcomes which will help these companies to advance their sustainability practice through inter-organisational learning, to enhance their mutual understanding and to strengthen their business partnerships over time, thus achieving holistic sustainability. This research contributes to scholarly understanding of tensions in sustainability between firms in collaborative business partnerships in relation to the nature of the tensions, reasons for the tensions, managerial sensemaking of tensions and the strategies for managing the tensions. This also adds value to paradox theory and organisational ambidexterity theory including structural and contextual ambidexterity, and their theoretical and practical implications for tensions in sustainability research.
Keywords: Sustainable development; China; New Zealand; Business enterprises; Environmental aspects; Partnership; Executives; Attitudes; 350706 International business